Branding of free-to-air television stations: from customer-based to audience-based brand equity / Zakaria Razalli - Razalli, Zakaria (Institute of Graduate Studies, UiTM, 2016)
The concept of Customer Based Brand Equity (CBBE) was introduced in 1990’s and since then there have been a few studies that apply the concept on television (TV) as media. Different characteristics of the business usually lead to different market structures at the industry level and in turn affect strategic choices at the firm’s level. Therefore, some scholars in the mass communication field pointed out of the need to study the applicability of brand equity constructs on broadcast television as a medium due to the unique nature of television as opposed to other products and services. This study seeks to examine comprehensively what drives brand equity in a TV media environment particularly for free-to-air TV channels and how it is operationalised among two key stakeholders, namely the channel management and the audience. The thesis has two parts…